From Marracott to Munksnäs. Literary Suburbia and the Architecture of Finnish Modernity in Kjell Westö’s Melba, Mallinen och jag and Drakarna över Helsingfors - Bassini, Alessandro (Folia Scandinavica Posnaniensia, 2025)
The purpose of this paper is to analyse the short story Melba, Mallinen och jag (1992) and the novel Drakarna över Helsingfors (1996) by Kjell Westö, with focus on the description of the suburbs of Munksnäs and Munkshöjden in the 1960s and 1970s. These two decades represent a pivotal moment in the history of Finland, as the country began to implement a fully capitalistic economy that led to radical socio-economic and cultural changes. From this perspective, the suburbs appear to be the ideal setting in which the new social hierarchy is established and the new economic dynamics unfold, with unavoidable conflicts and social tensions. Drawing on the neo-Marxist theory of Marshall Berman and recent studies on suburbs in city planning and literature, this paper aims to place the post-war Finnish suburbs in the literary tradition that started with Haussmann’s renovation of Paris as portrayed by Baudelaire in Le Spleen de Paris (1869).